India’s democracy: the competitive authoritarian propensity? - Mukherji, Rahul; Zarhani, Seyed Hossein (Pacific affairs, 2023)
This paper explains and corroborates the mechanisms by which civic and political spaces opposed to Hindu nationalism have been attacked, especially after the arrival of the right-wing Hindu nationalist Bharatiya Janata Party (BJP) government in 2014. Three mechanisms are discerned for - replacing pluralistic values with Hindu majoritarian ones. Sometimes institutions are just allowed to drift by interpreting old rules in new ways. For example, no formal rules for media control have changed but the government???s control over media has increased substantially. At other - times, incremental legal and policy changes are executed to make the change explicit, often building on a new moral purpose. To give another example, the Foreign Contribution Regulation Act (FCRA) was amended and weaponized against NGOs in a layered way in 2020. Finally, when political opposition - is weak, institutions that have provided guarantees for protecting diversity have simply been displaced by new and radically different ones. This was the case with abrogating Article 370, which converted the special status of the subnational state of Jammu and Kashmir to the status - of two federally administered union territories-Jammu and Kashmir and Ladakh. These mechanisms place India in a competitive authoritarian frame, where those in power deploy electoral majorities to systematically attack the political opposition, making it more di(cult for it to rise. - Despite these propensities, opposition parties have won elections in some of India’s subnational states. The challenges facing the world’s most populous democracy are significant, even though competitive elements co-exist. These elements in a competitive authoritarian regime, however, - are under severe stress. India’s democratic credentials can be revived only if the competitive elements of India’s democracy stand united against ethno-nationalist Hindu majoritarianism.